Cytomorphological study of the health status of Stepnogorsk city’s population - Duzbayeva, N.M.; Shokabayeva, A.S. (Fundamental and Experimental Biology, 2022)
The article evaluates the cytomorphological state of the rhinocytogramand buccal epithelium of the population living in the territory of Stepnogorsk, which is affected by adverse environmental factors. Cytomorphological research methods were used to determine the cytological state of the nasal cavity and mucous membranes in the population on the territory of Stepnogorsk. The obtained cytomorphological results revealed changes in the structural elements that perform the functions of a protective barrier as an integral part of the mucociliary system on the rhinocytogram and the BESCH cytogram. In the population living in Stepnogorsk, an increase in the number of flat epithelial cells damaged by the nasal mucosaby 17.1 times, by 14.1 times-in the affected cuboid and cylindrical epithelial cells, respectively, as well as an increase in the number of epithelial cells with apoptotic bodies in the buccal epithelium by 5.9 times, cells witha sign of karyorrhexis by 2.2 times, dual-core cells by 6.8 times reveal violations of the reparative process of the upper respiratory tract and contribute to the development of chronic pathology. Thus, noninvasive cytomorphological examination of smears of the nasal mucosa and buccal epithelium of the cheeks in residents living in ecologically unfavorable areas revealed the early manifestation of metabolic and pathogenetic changes.